Graphene-Based Assemblies for Moist-Electric Generation - Chen, Qing; Zhao, Jian; Cheng, Huhu (Frontiers in Energy Research, 2021)
Moisture is a ubiquitous and clean resource in nature, which continuously diffuses in the atmosphere and demonstrates huge chemical potential energy that is difficult to be utilized. Recently, the generation of power from interactions between graphene and gaseous water molecules in moisture has triggered great research interest that could provide a novel energy conversion system for our society. graphene-based assemblies have been considered as ideal platforms for moist-electric generation (MEG) in many studies, because of the abundant of functional groups, controllable microstructure and diverse macro morphologies. Therefore, in this short review, we will first state the preparation techniques of graphene-based assemblies for MEG. Then, the fundamental mechanisms of MEG are discussed and the latest advances on graphene MEG are reviewed. Finally, an overview of the current challenges and future development trends in graphene MEG is provided.